Oxidative Stress in an African Ground Squirrel, a Case of Healthy Aging and Reproduction - Paul Juan Jacobs; Sjoerd Vos; Chelsea E. Bishop; Daniel William Hart; Nigel Charles Bennett; Jane M. Waterman (Antioxidants)
Oxidative stress plays a crucial role in mediating life-history processes, where it can compromise survival and reproduction through harmful alterations to DNA, lipids, and proteins. In this study, we investigated oxidative stress in Cape ground squirrels (Xerus inauris), a longer-lived African ground squirrel species with a high reproductive skew and unique life history strategies. We measured oxidative stress as total antioxidant capacity (TAC), total oxidant status (TOS), and an oxidative stress index (OSI) in blood plasma from individuals of approximately known ages. Our results reveal a distinct pattern of decreasing oxidative stress with age, consistent across both sexes. Females exhibited lower OSI and TOS levels than males. Males employing different life-history strategies, namely natal (staying at home), had significantly lower oxidative stress compared to the band (roaming male groups), likely due to variations in metabolic rate, activity, and feeding rates. However, both strategies exhibited reduced oxidative stress with age, though the underlying mechanisms require further investigation. We propose that selection pressures favoring survival contributed to the observed reduction in oxidative stress with age, potentially maximizing lifetime reproductive success in this species.